The Cuban cooperative movement and its foundation in the ideological legacy of Fidel Castro Ruz (REDEL. Revista Granmense de Desarrollo Local, 2025)
To carry out the socialist transformation of Cuban agriculture and to fulfill one of the issues raised in the Moncada Program, Commander in Chief Fidel Castro granted peasants a portion of the lands confiscated from large landowners and, years later, invited them to join the agricultural cooperatives that were established to further integrate them into the process of building socialism and strengthening the worker-peasant alliance. This article aims to reflect on the development of the Cuban cooperative movement across its different stages, using Fidelist thought as the guiding thread. For this purpose, the universal dialectical materialist theoretical method and its specific methods were used: the unity of the logical and the historical, analysis and synthesis, as well as scientific abstractions. These methods were employed to analyze, in a periodized manner, the development of the cooperative process in Cuba and to understand that, under the leadership of Fidel Castro, the Cuban Revolution found in agricultural cooperativism a key model of cooperation, effective for modernizing crop production and for the collective use of land.
Keywords: agricultural cooperatives; agricultural development; Fidel Castro; Cuban cooperative movement.